An Assessment of Zakat Contributions for Productive Purposes to Empower the Mustahik Economy in the Face of the Covid-19 Pandemic (UIN Sunan Kudus, 2021)
People have lost their jobs as a result of the Covid-19 pandemic, and many people are now living in poverty. Zakat is one of the Islamic pillars concerned with poverty reduction, particularly in the form of productive disbursement. The purpose of this research is to identify and assess the mechanisms and contributions of productive zakat to economic empowerment mustahik during the covid-19 pandemics. Zakat for productive purposes is wealth that enables the recipient to continuously create creativity using zakat funds. This study conducted in-depth interviews with three Zakat institution staff and seven mustahik who live in a low-income society and are economically impacted by covid-19. This study used the descriptive method, with data retrieval in this study using the interview method, followed by data analysis in the form of data reduction, data presentation, and conclusions. According to the findings of this study, there are still a limited number of Human Resources available for mustahik coaching and supervision at LAZISMU Pemalang. This paper discovered that not all mustahik use 100 percent of productive zakat funds to develop the business as hoped, but instead meet basic needs. Mustahik primarily requires more fulfillment with short-term benefits in order to sustain their lives.